2012
DOI: 10.1007/s00018-011-0911-3
|View full text |Cite
|
Sign up to set email alerts
|

The primary cilium as a dual sensor of mechanochemical signals in chondrocytes

Abstract: The primary cilium is an immotile, solitary, and microtubule-based structure that projects from cell surfaces into the extracellular environment. The primary cilium functions as a dual sensor, as mechanosensors and chemosensors. The primary cilia coordinate several essential cell signaling pathways that are mainly involved in cell division and differentiation. A primary cilium malfunction can result in several human diseases. Mechanical loading is sense by mechanosensitive cells in nearly all tissues and organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 86 publications
0
62
0
2
Order By: Relevance
“…Ultrastructural studies have confirmed that mature chondrocytes possess an immotile primary cilium that has a microtubule axoneme core made up of a ring of nine microtubule doublets, but devoid of the central pair of microtubules (thus designated as 9+0) that motile cilia always have (called a 9+2 axoneme) [26]. Primary cilia have been well documented to serve as a nexus that integrates chemical and mechanical signals; in particular, they are considered as mechanosensors of fluid flow in many cell types including kidney epithelial cells, cholangioctyes or endothelial cells [54].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ultrastructural studies have confirmed that mature chondrocytes possess an immotile primary cilium that has a microtubule axoneme core made up of a ring of nine microtubule doublets, but devoid of the central pair of microtubules (thus designated as 9+0) that motile cilia always have (called a 9+2 axoneme) [26]. Primary cilia have been well documented to serve as a nexus that integrates chemical and mechanical signals; in particular, they are considered as mechanosensors of fluid flow in many cell types including kidney epithelial cells, cholangioctyes or endothelial cells [54].…”
Section: Discussionmentioning
confidence: 98%
“…Primary cilia have been well documented to serve as a nexus that integrates chemical and mechanical signals; in particular, they are considered as mechanosensors of fluid flow in many cell types including kidney epithelial cells, cholangioctyes or endothelial cells [54]. Primary cilia are also present on human mesenchymal stem cells, on arthritic chondroprogenitor cells (CPCs) [26] and on chondrocytes where they are unique sensory organelles that project into the pericellular matrix and interact with their close environment (i.e. collagen types II and IV) via integrins, G proteins, and various Ca 2+ channels; many of which have been implicated as mechanoreceptors [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary cilia in chondrocytes acts as a mechanosensor, (17) and the polycystic kidney disease 2 (Pkd2) gene encodes a mechanoreceptor localized on cilia. Conditional loss of Pkd2 leads to multiple postnatal craniofacial anomalies, including the compression of temporomandibular joints when heads receive a mechanical stress.…”
Section: Discussionmentioning
confidence: 99%
“…Ion channels, integrin signaling, and the primary cilia have all been implicated in transducing the external biophysical environment of chondrocytes into electrical and/or chemical intracellular signaling (7)(8)(9). Specifically, intracellular Ca 2+ signaling has emerged as a common regulatory mechanism for controlling gene and protein expression (10)(11)(12).…”
mentioning
confidence: 99%